PENGARUH PENDAPATAN TERHADAP KONSUMSI NELAYAN BAGAN DI KAMPUNG TANJUNG BATU KECAMATAN PULAU DERAWAN: PENGARUH PENDAPATAN TERHADAP KONSUMSI NELAYAN BAGAN DI KAMPUNG TANJUNG BATU KECAMATAN PULAU DERAWAN - Ika Rosmalina (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2020)
The purpose of the research is to determine the influence of revenue on the consumption of Bagan fishermen in Kampung Tanjung Batu subdistrict Derawan Island. The research was conducted to 75 people in the chart as respondents. The analysis tool used in this study is a simple linear regression analysis. Based on the results of the research can be noted that the amount of income partially influential and positive against the consumption of bagan fishermen in Kampung Tanjung Batu Sub-district Derawan Island. The consumption function indicates the relationship between the revenue variable and the consumption variable where the consumption formula obtained is C = 0.704 + 0.586 Y. Of such equations can be known amount of consumption made at the time of the fishermen income chart Equal to zero hence consumption of fishermen family there is 0.704 or (in million rupiah) Rp. 704,000 and the value 0.586 or 58.6% meaning there is an addition to consumption at the time of increasing revenues and the remainder of 41.4% is used for savings.